Intellectual Capital Disclosure Analysis based on Profitability in Tourism and Hospitality Sector in Indonesia and Thailand - Saarce Elsye Hatane; Naomi Lamiki; Victoria Stephanie (Jurnal Ilmiah Akuntansi, 2021)
This research aims to investigate the level of disclosure of intellectual capital components in tourism and hospitality companies in Indonesia and Thailand. We use intellectual capital components and profitability levels as variables. This research analyzes the differences in the level of disclosure of intellectual capital components between tourism and hospitality companies in Indonesia and Thailand that fall into the category of having high profitability and companies that fall into the category of having low profitability. This research uses One-Sample Kolmogorov-Smirnov Test and Wilcoxon Signed Ranks Test to analyze the data. The results showed significant differences in the disclosure of intellectual capital components in tourism and hospitality companies in Indonesia and Thailand. Human Capital is the component with the highest level of disclosures. Companies classified as having high profitability tend to disclose more about intellectual capital than companies classified as having low profitability.